Superresolution of Images Using Area Preserving Geometric Evolution Laws. (15th December 2011) - Jäger Jäger, Caroline Caroline; Praetorius Praetorius, Simon Simon; Voigt Voigt, Axel Axel
Abstract : PDE-based approaches are used to obtain superresolution of images. Using level set method for area constraint geometric evolution laws allows to remove pixelation in images without removing small-scale features. We compare mean curvature flow, surface diffusion, and Willmore flow for this purpose.